Utilization of Chili Citrus (Citrus microcarpa) as a Natural Fixator for Dyeing Cotton Fabrics with Dayak Onion Tuber Extract (Eluetherine palmifolia (L.) Merr) - Widyasari, Ida Ayu Made Tania; Masriani, Masriani; Hairida, Hairida (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The high demand for the textile industry can pollute the environment through waste. Natural dyes from natural ingredients are used as a step to minimize this waste.  Dayak onions can be used as a natural dye because they produce a red color from anthocyanin compounds. However, natural dyes have weaknesses, namely that the color is less stable and fades easily, so a fixator is needed. Fixator is used to strengthen the color in fabrics that use natural dyes. Orange chili sauce has the potential to be a natural fixator because it contains citric acid. This research aims to analyze the effect of the concentration of chili pepper fixator (Citrus microcarpa) on the color fastness of cotton fabric using natural dyes from Dayak onion bulbs (Eleutherine palmifolia (L.) Merr). The research method used was an experiment using a colorimeter application whose results were in the form of ΔE values. The test was carried out on the color of the fabric that had been dyed and fixed and then the average value (ΔE) was measured before and after washing the soap. The research results showed that the average value (ΔE) of the smallest to largest fixator was a concentration of 20%, 100%, 0%, 40%, 60% and 80%. Based on the results of the Kruskal Wallis test followed by the Bonferroni test, a significant value of 0.024 (p>0.05) was obtained at a concentration of 20%. This shows that the chili lime fixator has a significant influence on the fastness of the fabric.